FIM moves to new building - Sorooshian, Shahryar; M., Waris; Senthil Kumar , T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (FIM-UMP, 2016)
During the first quarter of 2016, FIM started functioning from the new premises at the KPU Building, Gambang, located opposite to Taman Teknologi & Inovasi.